Keanekaragaman Masyarakat Indonesia - Y, Yunita; Pangestoeti, Wahjoe; Ramadhani, Bella; Syalsabila, Keysa Dwina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
With around 267 million inhabitants in SUPAS 2019, Indonesia is the fourth most densely populated nation behind the United States. Its population is diverse in terms of social, religious, ethnic, and cultural backgrounds. There are various variables that influence the variety of Indonesian society, and it comes from within and outside the community itself. The integrity of the Indonesian nation may be threatened by this challenge of such variety. This study uses a descriptive qualitative approach to assess diversity using a single Bhinneka framework. This study use a library technique to gather literature related to the research that is being conducted. The study's findings demonstrate that, in the current state of affairs, efforts to strengthen ties between tribal, religious, and other social groups can be made via collaboration utilizing the equality, respect, and equality tenets found in Bhinneka Singh Ika's framework for the national integration of the Indonesian people.